Efecto de la eliminacion de organos florales en hibridos y variedades de maiz tropical - Balderas Muñoz, M.=700 1 Ramirez Vallejo, P.; Geron Xavier, F.
(Es, En)
Ilus., 12 ref.
Keywords: ZEA MAYS; ELIMINACION DE FLORES; ESPIGAS; VARIEDADES; HIBRIDOS; MEXICO; JILOTE; REVISTA CHAPINGO